Unilateral ophthalmoplegia in anti-GQ1b antibody syndrome: case report and systematic literature review - Pan, Juyuan; Zheng, Ningyu; Yu, Dan; Jiang, Huihua; Zhou, Yuanlin (Frontiers in Immunology, 2025)
IntroductionAnti-GQ1b antibody syndrome encompasses immune-mediated neuropathies targeting ganglioside GQ1b, classically presenting as Miller Fisher syndrome (MFS) with the triad of ophthalmoplegia, ataxia, and areflexia. While bilateral ophthalmoplegia is typical, unilateral presentations represent a recognized variant phenotype.MethodsWe report a case of a 17-year-old male with unilateral complete oculomotor nerve palsy, confirmed by positive serum anti-GQ1b IgG antibodies. We also conducted a literature review identifying 17 additional cases of anti-GQ1b associated unilateral ophthalmoplegia, summarizing clinical features, investigations, management, and outcomes for all 18 patients.ResultsAmong the 18 patients, a male predominance was observed (13 males, 5 females), with a median age of 31 years (range 10-68). Most patients (17/18, 94.4%) reported a preceding illness. Unilateral external ophthalmoplegia was universal, most commonly affecting adduction (55.6%) and vertical gaze (55.6%). Internal ophthalmoplegia (IO) occurred in 6 cases (33.3%), including 4 unilaterally. Cerebrospinal fluid (CSF) protein was mildly elevated (23–97 mg/dL) in 7 of 18 cases. Treatments varied and prognosis was uniformly favorable, with most patients recovering within 3 months.ConclusionUnilateral ophthalmoplegia, particularly when complicated by ipsilateral internal ophthalmoplegia, constitutes a distinct regional variant of anti-GQ1b antibody syndrome. Early serological testing for anti-GQ1b antibodies is key to diagnosis, especially in patients with antecedent infection.